Distinct phasic and sustained brain responses and connectivity of amygdala and bed nucleus of the stria terminalis during threat anticipation in panic disorder. Issue 15 (9th May 2017) - Brinkmann, L.; Buff, C.; Feldker, K.; Tupak, S. V.; Becker, M. P. I.; Herrmann, M. J.; Straube, T.
Abstract : Background: Panic disorder (PD) patients are constantly concerned about future panic attacks and exhibit general hypersensitivity to unpredictable threat. We aimed to reveal phasic and sustained brain responses and functional connectivity of the amygdala and the bed nucleus of the stria terminalis (BNST) during threat anticipation in PD. Methods: Using functional magnetic resonance imaging (fMRI), we investigated 17 PD patients and 19 healthy controls (HC) during anticipation of temporally unpredictable aversive and neutral sounds. We used a phasic and sustained analysis model to disentangle temporally dissociable brain activations. Results: PD patients compared with HC showed phasic amygdala and sustained BNST responses during anticipation of aversive v . neutral stimuli. Furthermore, increased phasic activation was observed in anterior cingulate cortex (ACC), insula and prefrontal cortex (PFC). Insula and PFC also showed sustained activation. Functional connectivity analyses revealed partly distinct phasic and sustained networks. Conclusions: We demonstrate a role for the BNST during unpredictable threat anticipation in PD and provide first evidence for dissociation between phasic amygdala and sustained BNST activation and their functional connectivity. In line with a hypersensitivity to uncertainty in PD, our results suggest time-dependent involvement of brain regions related to fear and anxiety.